Evaluation of lumbosacral orthosis in flexion and extension movements of lumbar spine / Norazian Abd Razak - Norazian, Abd Razak (2010)
Lumbosacral orthosis (LSO) is a type of spinal orthosis that has been recommended for abdominal support, pain management, and motion or positional control. By implemented radiographic technique, objectives of this study was to evaluate the changes of lumbar lordosis in flexion and extension of trunk movements with and without wearing the LSO measured by Cobb, Centroid, and Posterior Tangent techniques and to correlate the value of lordotic angles in particular posture. Ten healthy male subjects without any history of low back pain participated and a semi-rigid LSO was utilized. Antero-posterior and lateral radiographs of spine images during neutral, flexion, and extension postures, with and without LSO, were captured. Lateral radiographic images were observed by five observers to determine the lumbar lordosis angles by implementation of Cobb, Centroid, and Posterior Tangent methods. Hand drawn line technique was applied on each image using a ruler while lordotic angles were measured using a protractor. Statistical analysis was completed using SPSS (Statistical Package for the Social Sciences). Lumbar lordoses ranged from 6.16° to 14.88° without orthosis and 15.24° to 17.92° with orthosis for trunk flexion and as for trunk extension with and without orthosis, lumbar lordoses ranged from 39.92° to 57.96° and 36.24° to 56.88°, respectively. Correlation between the methods was significant. In addition, there was a significant difference between lumbar lordosis of trunk flexion measured by Cobb and Centroid techniques. However, there were only small changes in trunk extension with and without orthosis measured by Cobb, Centroid, and Posterior Tangent methods. Reliability among observers was also high. Present results indicate that the lumbar lordo is increased when the lumbosacral orthosis was used in both flexion and extension postures.